›On Avoiding Distress‹ and ›On My Own Opinions‹ - Polemis, Ioannis; Xenophontos, Sophia (Trends in Classics - Supplementary Volumes, 2023)
This volume provides a new critical edition of Galen's On Avoiding Distress and On My Own Opinions, which represents an improvement on earlier editions by offering more accurate readings of the main witness Vlatadon 14, supplementation of previously unrestored lacunae, and many sound emendations to thorny passages. The authoritative critical texts are accompanied by English translations, making the works accessible for further consultation.